Formulación y elaboración de una bebida a base de semillas de chía (salvia hispánica l.) con inulina, edulcorada con estevia y sacarosa - Calderón Paladines, Henry Franco; Álava Pesantes, Jonathan Xavier (My University, 2025)
The growing consumer demand for healthy products that, in addition to providing essential nutrients, offer additional health benefits has driven the development of innovative functional foods. In this context, the present research aims to formulate and develop a chía-based beverage enriched with inulin and sweetened with stevia or sucrose, with the goal of evaluating its sensory acceptance and physicochemical characteristics. The base beverage was formulated with 1.5% chia, plus preservative, flavoring, and coloring. From this base, six treatments were formulated: T1 (3% inulin, sucrose), T2 (3% inulin, stevia), T3 (5% inulin, sucrose), T4 (5% inulin, stevia), T5 (7% inulin, sucrose), and T6 (7% inulin, stevia). Sensory evaluation of the formulations was conducted with 42 semi-trained panelists. In the first phase, a hedonic test was used to assess texture, flavor, aroma, and appearance; in the second phase, a preference test was conducted. The samples with the highest overall acceptability were subjected to physicochemical analysis of the final product. The results from the sensory evaluation demonstrate that formulations T5 (7% inulin, sucrose) and T6 (7% inulin, stevia) showed the highest overall sensory acceptability, with no significant differences between them but with significant differences compared to T1, T2, T3, and T4, particularly in attributes such as texture, flavor, aroma, and appearance. The physicochemical analysis of samples T5 and T6 indicates that the product meets the established regulatory requirements: pH (T5 y T6= 4.36 ±0.057), soluble solids (T5 = 12.83 ± 0.15 °Brix; T6 = 7.96 ± 0.057 °Brix), and acidity (T5 and T6 = 0.95 ± 0.20 meq/kg). Additionally, nutritional labeling parameters were determined, including total sugar content by HPLC (T5 = 7.77% and T6 = 1.32%), sodium (T5 = 35.15 ± 0.00 mg and T6 = 62.48 ± 6.76 mg), and fat (0,46) theoretical calculation. Moreover, the nutritional analysis revealed that the beverage is high in dietary fiber (7.18%), highlighting its prebiotic potential. These results indicate that the chía-based beverage enriched with inulin is not only sensorially accepted but also meets nutritional quality standards, positioning it as a healthy alternative in the development of functional foods.
La creciente demanda de los consumidores por productos saludables que, además de aportar nutrientes esenciales, ofrezcan beneficios adicionales para la salud, ha impulsado el desarrollo de alimentos funcionales innovadores. En este contexto, el presente trabajo de investigación tiene como objetivo la formulación y elaboración de una bebida a base de chía enriquecida con inulina y edulcorada con estevia o sacarosa con el fin de evaluar su aceptación sensorial y características fisicoquímicas. Se formuló la bebida base con 1,5% de chía más conservante, saborizante y colorante, a partir de esta base se formuló 6 tratamientos T1 (3% inulina, sacarosa), T2 (3% inulina, estevia), T3 (5% inulina, sacarosa), T4 (5% inulina, estevia), T5 (7% inulina, sacarosa), y T6 (7% inulina, estevia). Se realizó la evaluación sensorial de las formulaciones con 42 panelistas semientrenados: primera fase se utilizó una prueba hedónica para la evaluación de textura, sabor, aroma y apariencia; en la segunda fase se utilizó una prueba de aceptación general. De las muestras con mayor aceptabilidad global se analizó las propiedades fisicoquímicas del producto final. Los resultados obtenidos de la evaluación sensorial muestran que T5 (7% inulina, sacarosa) y T6 (7% inulina, estevia) fueron los más aceptados, con diferencias significativas respecto a los demás tratamientos en textura, sabor, aroma y apariencia. En cuanto a los resultados de los análisis fisicoquímicos de las muestras T5 y T6 indican que el producto cumple con los requisitos establecidos en la norma: pH (T5y T6= 4,36 ±0,057), sólidos solubles (T5=12,83 ±0,15 °Brix ; T6= 7,96 ±0,057 °Brix) y acidez (T5 y T6 = 0,95 ±0,20 meq/kg). Además, se determinó los parámetros establecidos en el semáforo nutricional el contenido de azucares totales mediante HPLC (T5= 7,77% y T6=1,32%), sodio (T5=35,15 ±0,00) y grasas (0,46) cálculo teórico. Además, el análisis nutricional reveló que la bebida es rica en fibra dietaria (7,18%), lo que resalta su potencial prebiótico. Estos resultados indican que la bebida a base de chía enriquecida con inulina no solo es sensorialmente aceptada, sino que también cumple con los estándares de calidad nutricional, consolidándose como una alternativa saludable en el desarrollo de alimentos funcionales.
Keywords: CHIA; INULINA; ESTEVIA; FIBRA DIETARIA